Pengaruh Rata Rata Lama Sekolah Terhadap Pertumbuhan Ekonomi di Provinsi Sumatera Utara: Penelitian - Zackya Hayati Lubis; Laurent Damai Yanti Silaban; Claudia Tabitha Panjaitan; Olivia Damayanti Marpaung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the effect of average years of schooling (ALS) on economic growth in North Sumatra Province for the period 2009–2024. Education is believed to improve human resource quality and productivity, but although ALS increased from 8.29 years (2009) to 9.93 years (2024), economic growth actually fluctuated and contracted in 2020 due to the COVID-19 pandemic. The method used was simple linear regression with the EViews 10 application using secondary data from BPS. The dependent variable was economic growth (Y) based on a constant GRDP rate, while the independent variable was ALS (X). The results showed that ALS had no significant effect on economic growth, with a regression coefficient of -15.68645 and a probability of 0.0706. The R² value of 0.214793 indicated that only 21.47% of the variation in economic growth was explained by ALS, the remaining 78.53% was influenced by other factors. This finding confirms that increasing RLS is not enough to drive economic growth, so education policies need to be accompanied by job creation, improving the quality of learning, and workforce absorption.